2011
DOI: 10.1007/s00408-011-9338-8
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphisms in GSTM1, CYP1A1, CYP2E1, and CYP2D6 are Associated with Susceptibility and Chemotherapy Response in Non-small-cell Lung Cancer Patients

Abstract: Our findings support the hypothesis that a polymorphism in GSTM1 is associated with lung cancer susceptibility. Furthermore, polymorphisms in GSTM1 and CYP1A1 were associated with chemotherapy response. In particular, smokers carrying deficient-type GSTM1 were at a higher risk of developing lung cancer. Patients carrying deficient-type GSTM1 responded better to platinum drugs, while those with TT CYP1A1 were better responders to nonplatinum drugs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 27 publications
0
27
0
1
Order By: Relevance
“…However, after screening of the titles and abstracts of all 114 articles, 50 were excluded. Of the 64 potentially relevant articles identified for further assessment, one article (Wu et al, 2003) was excluded because it did not provide sufficient data about the distribution of GSTM1 genotype, 18 Hu et al, 1998;Chen et al, 1999;Gu et al, 2004;Luo et al, 2004;Ye et al, 2005;Zeng et al, 2005;Chang et al, 2006;Wang et al, 2007;Chang et al, 2009;Li et al, 2011;Li et al, 2012;Ma et al, 2013) were excluded because they concerned duplicate subjects. Finally, a total of 45 articles (47 studies) (Ge et al, 1996;Gao & Zhang, 1999;Lan et al, 2000;London et al, 2000;Chen et al, 2001;Zhao et al, 2001;Chan et al, 2002;Lu et al, 2002;Zhang et al, 2002a;Chen et al, 2003;Xian et al, 2003;Chan-Yeung et al, 2004;Li et al, 2004;Liang et al, 2004;Yang et al, 2004;Chan et al, 2005;Li et al, 2005a;Qiao et al, 2005;Wang et al, 2005;Chen et al, 2006;Qian et al, 2006;Yao et al, 2006;Gu et al, 2007;Lei et al, 2007;Liu et al, 2008;…”
Section: Study Selectionmentioning
confidence: 99%
“…However, after screening of the titles and abstracts of all 114 articles, 50 were excluded. Of the 64 potentially relevant articles identified for further assessment, one article (Wu et al, 2003) was excluded because it did not provide sufficient data about the distribution of GSTM1 genotype, 18 Hu et al, 1998;Chen et al, 1999;Gu et al, 2004;Luo et al, 2004;Ye et al, 2005;Zeng et al, 2005;Chang et al, 2006;Wang et al, 2007;Chang et al, 2009;Li et al, 2011;Li et al, 2012;Ma et al, 2013) were excluded because they concerned duplicate subjects. Finally, a total of 45 articles (47 studies) (Ge et al, 1996;Gao & Zhang, 1999;Lan et al, 2000;London et al, 2000;Chen et al, 2001;Zhao et al, 2001;Chan et al, 2002;Lu et al, 2002;Zhang et al, 2002a;Chen et al, 2003;Xian et al, 2003;Chan-Yeung et al, 2004;Li et al, 2004;Liang et al, 2004;Yang et al, 2004;Chan et al, 2005;Li et al, 2005a;Qiao et al, 2005;Wang et al, 2005;Chen et al, 2006;Qian et al, 2006;Yao et al, 2006;Gu et al, 2007;Lei et al, 2007;Liu et al, 2008;…”
Section: Study Selectionmentioning
confidence: 99%
“…Studies investigating the effect of the CYP2E1*5B polymorphism on NSCLC risk also reported inconsistent results (17,(28)(29)(30)(31)(32).…”
Section: Discussionmentioning
confidence: 99%
“…However, individuals not exposed to these risk factors can also develop lung cancer, indicating that a difference in cancer susceptibility exists among individuals (Ada et al, 2012). Previous studies indicate that genetic polymorphisms in the glutathione S-transferase M1 (GSTM1) gene may affect the risk of lung cancer (Nakachi et al, 1993;Cao et al, 2004;Chen et al, 2004aChen et al, , 2012Atinkaya et al, 2012;Han et al, 2012;Li et al, 2012;Liang et al, 2012;Liu et al, 2012). Subjects who have inherited specific variants in the GSTM1 gene may be susceptible to the effects of chemical carcinogens and thus at a high risk of developing lung cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Seidegård et al (1986) first reported the association between GSTM1 deficiency and lung cancer. Since then, there have been more than 40 studies examining this topic (Li et al, 2012;Liang et al, 2012;Liu et al, 2012;López-Cima et al, 2012;Yao et al, 2012). However, there is disagreement among the results of these studies.…”
Section: Introductionmentioning
confidence: 99%